Pengelolaan, Tugas dan Fungsi Badan Permusyawaratan Desa (BPD) - Ifrani Ifrani (Jalujur: Jurnal Pengabdian Masyarakat, 2022)
AbstractThe Village Consultative Body (BPD) is an institution that embodies democracy in the administration of village governance. The BPD can be considered as the "parliament" of the village. BPD is a new institution in the village in the era of regional autonomy in Indonesia. BPD as a village institution has strategic roles and functions as well as tasks because it can carry out checks and balances in the administration of government in the village as mandated by Law no. 6 of 2014 concerning Villages to realize the welfare of rural communities. This also creates a new paradigm in village administration. Village administrators with the existing system experience obstacles such as a lack of understanding of the laws and regulations as a guide in carrying out their duties and functions. The influence of human resources is the main factor in determining the quality and capacity of BPD members. This service is also present as a form of concrete steps in helping to improve human resources as members of the BPD, Village Heads and Village Apparatuses, especially in Hulu Sungai Utara Regency. So that this service proposal is an effort to be able to maximize the human resources of the BPD, the Village Head and the Village Apparatus through training and technical guidance, namely by providing an explanation of the material in tutorials and discussions. Abstrak Badan Permusyawaratan Desa (BPD) merupakan lembaga perwujudan demokrasi dalam penyelenggaraan pemerintahan desa. BPD dapat dianggap sebagai "parlemen"-nya desa. BPD merupakan lembaga baru di desa pada era otonomi daerah di Indonesia. BPD sebagai lembaga desa mempunyai peran dan fungsi serta tugas yang strategis karena dapat melakukan check and balance pada penyelenggaran pemerintahan di Desa sebagaimana amanat Undang-Undang No. 6 Tahun 2014 tentang Desa untuk mewujudkan kesejahteraan masyarakat desa. Hal ini pun menimbulkan paradigma baru dalam penyelenggaran desa. Penyelenggara desa dengan sistem yang ada mengalami kendala seperti kurangnya pemahaman akan peraturan perundang-undangan sebagai panduan dalam menjalankan tugas dan fungsinya. Pengaruh sumber daya manusia menjadi faktor utama dalam menentukan kualitas dan kapasitas anggota BPD. Pengabdian ini pun hadir sebagai bentuk langkah nyata dalam membantu meningkatkan sumber daya manusia sebagai anggota BPD, Kepala Desa serta Aparatur Desa khususnya di Kabupaten Hulu Sungai Utara. Sehingga usulan pengabdian ini sebagai upaya untuk dapat memkasimalkan sumber daya manusia BPD, Kepala Desa serta Aparatur Desa melalui pelatihan dan bimbingan teknis, yaitu dengan memberikan penjelasan materi secara tutorial dan diskus.